Integration failure of regenerated limb tissue is associated with incongruencies in positional information in the Mexican axolotl - Vieira, Warren A.; Raymond, Michael; Kelley, Kristina; Cherubino, Matthew A.; Sahin, Hande; McCusker, Catherine D. (Frontiers in Cell and Developmental Biology, 2023)
The Mexican axolotl is a powerful model organism to study limb regeneration because it is capable of regenerating complete limbs as adults. When the limb is amputated, it forms a transient regenerative organ known as the blastema at the site of injury, which will grow and form the missing limb structures. Little is known about how the newly regenerated limb tissues seamlessly integrate with the remaining stump tissues to form a functional structure, and why this doesn't occur in some regenerative scenarios. In this study, we evaluate the phenomenological and transcriptional characteristics associated with integration failure in ectopic limb structures generated by treating anterior-located ectopic blastemas with Retinoic Acid (RA). Our data shows that the RA-induced ectopic tissue has characteristics of both limb and flank tissue. We also observed disparities in “limb” Hox gene expression between the host site and the ectopic limb tissues which correlate with the timepoints when integration failure occurs. Together, these findings suggest that inconsistencies in positional information may underlie integration failure of RA-induced ectopic structures. Finally, we extrapolate on the observed asymmetry of anterior/posterior information along the proximal/distal limb axis to test the hypothesis that the posterior portion of the most proximal region of the limb contains anterior positional identities. Together these experiments provide valuable insight into the underlying causes of integration failure and further map the distribution of positional identities in the mature limb.